Nanotechnology in Reconstructive and Plastic Surgery - Mishra, Susant; Mishra, Binayak (International Journal of Psychosocial Rehabilitation, 2019)
Nanotechnology is relatively young field that have countless applications of biomedicine in use or under research. Many specialties have benefited from the refining of diagnostic and therapeutic techniques to the nanoscale. Translational nanotechnology-based medical devices and treatments are now being developed and implemented. It is expected that this new technology could be instrumental in future of plastic surgery. Microelectromechanical systems are the one form of nanotechnology that allows miniaturized implants to be developed for employ in the treatment of various clinical conditions. Reconstructive and plastic surgery is an incredibly varied specialty that includes craniofacial and manual surgery; oncological, congenital reconstruction and trauma; burn care and esthetic surgery. Nanotechnology developments have had a major impact on wound treatment, topical skin care, implant and prosthetic architecture, drug delivery systems and tissue engineering. Plastic surgeons are currently investigating the utility of nanoscale devices for bone reconstruction, drug delivery and bone prosthetics. Nanotechnology may continue to develop on previous developments and greatly extend its biomedical uses in reconstructive and plastic surgery.